2006
DOI: 10.1080/02652030500387554
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of heavy metals by vegetable plants grown on contaminated soil and their bioavailability in the human gastrointestinal tract

Abstract: Lettuce, spinach, radish and carrot were grown on compost that had previously been contaminated at different concentrations of Cd, Cu, Mn, Pb and Zn. Control plants of each vegetable were also grown on unadulterated compost. The experiment was carried out under greenhouse conditions. Mature plants were harvested and their roots and leaves collected. Soil samples from each growing pot and plant materials were acid digested and analysed to determine total metal concentration. Flame-Atomic Absorption Spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
138
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(151 citation statements)
references
References 37 publications
11
138
1
1
Order By: Relevance
“…The concentrations of heavy metals in plants largely depend on the concentrations of heavy metals in the soil (9,10). In our study, the overstepping of maximum levels for Cd and Pb in vegetable samples was most likely due to soil contamination with these heavy metals.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The concentrations of heavy metals in plants largely depend on the concentrations of heavy metals in the soil (9,10). In our study, the overstepping of maximum levels for Cd and Pb in vegetable samples was most likely due to soil contamination with these heavy metals.…”
Section: Discussionmentioning
confidence: 83%
“…A phytosanitary strategy has been created to set guidelines for the development of plant-health national policy in Croatia (60). Although various factors may contribute to elevated concentrations of heavy metals in food, soil contamination is one of the most important (9,10). A programme for permanent monitoring of the soil in Croatia has been developed; however, data regarding the state of the soil has still not been collected (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Pb mainly reaches leaves by aerial deposition. Likewise, the aerosol-deposited Pb particles do not penetrate the cuticle of leaves but tend to adhere to leaf surfaces (Caselles 1998;Intawongse and Dean 2006;Nabulo et al 2006;Kuang et al 2007). Basically, Pb content in crops grown in uncontaminated areas as cited by Umali (1999) and Flynn (1999) ranged from 0.1 to 10 ppm dry weight.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the total metal content was different among the digestion phases (HNO₃, gastric, intestinal, and residual). For example, the Mn bioaccessibility in the lettuce (Lactuca sativa L.) leaves decreased in the order of gastric > residual > intestinal [98], while [99] revealed that the solubility of Cd in the cock's comb (Celosia argentea L.) followed the order gastric > residual > intestinal. The bioaccessibility of metals from the different digestion phases is dependent on several factors such as the digestion and release of the ingested food matrix [100].…”
Section: First-second-third-fourth Phasesmentioning
confidence: 99%